Seasonal Variability in Benthic–Pelagic Coupling: Quantifying Organic Matter Inputs to the Seafloor and Benthic Macrofauna Using a Multi-Marker Approach - Rodil, Iván F.; Lucena-Moya, Paloma; Tamelander, Tobias; Norkko, Joanna; Norkko, Alf (Frontiers in Marine Science, 2020)
The exchange between the water column and the seafloor is a complex process, and is particularly intensive in the shallow waters of highly productive coastal areas, where the temporal variability in the inputs of pelagic organic matter will determine many aspects of the benthic community structure. However, few studies have focused on the seasonality of inputs of organic matter to the seafloor, and on the consequent dynamics and time scales of response of benthic consumers. We conducted a 1-year study where we repeatedly sampled multiple organic compounds traditionally used as markers to study the link between the pelagic organic matter inputs and the seafloor, and the potential response of benthic macrofauna to seasonal trends in phytoplankton biomass. We simultaneously quantified the particulate organic matter in the water column, the sinking material and different seafloor compartments, and analyzed it for pigments, organic carbon and nitrogen content, C/N ratio, and stable isotopes. Seafloor sediment was also analyzed for total lipids, and the dominant macrobenthic species for isotopic signatures. Results showed a major deposition of fresh organic matter during the spring bloom followed by more degraded organic matter inputs during the late summer bloom and even lower quality of the organic matter reaching the seafloor during winter. Strong positive relationships between water column and sedimentary pigments suggest that phytoplankton was the main source of carbon to the seafloor. The isotopic signatures of the dominant macrobenthic species suggest a fast response to the organic matter inputs from the water column. However, different species responded differently to the deposition of organic matter. Macoma balthica and Marenzelleria spp. fed on more reworked and degraded sedimentary material, while Monoporeia affinis showed a shift in the feeding habits according to its life stage, with adult individuals feeding on fresher material than juveniles did. Our study highlights the seasonal variability of the benthic–pelagic coupling and the utility of a multi-marker approach to follow the temporal inputs of organic matter from the water column to the seafloor and benthic organisms.